2005
DOI: 10.1002/chir.20106
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a tartaric acid‐based linear polyamide and dimer as chiral selectors in liquid chromatography

Abstract: A twin selector for enantioselective liquid chromatography based on O,O V-bis(dimethyl)benzoyl tartaric diamide was synthesized and compared to commercially available Kromasil CHI-DMB (O,O V-bis(dimethyl)benzoyl tartaric diamide). A linear polyamide based on the same tartaric acid derivative was also synthesized, immobilized on silica, and evaluated as stationary phase. The twin selector was immobilized as a brush-type phase, with similar bonding chemistry as in Kromasil CHI-DMB. It was shown to exhibit lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…To improve the enantioseparation ability, some biselector CSPs were reported. [12][13][14][15][16] However, these biselector CSPs do not always show enhanced enantioseparation ability. In the reported works, two chiral compounds were connected with a cross-linker of multiple reactive groups to form a biselector, which was then immobilized on a support to afford a biselector CSP.…”
Section: Introductionmentioning
confidence: 97%
“…To improve the enantioseparation ability, some biselector CSPs were reported. [12][13][14][15][16] However, these biselector CSPs do not always show enhanced enantioseparation ability. In the reported works, two chiral compounds were connected with a cross-linker of multiple reactive groups to form a biselector, which was then immobilized on a support to afford a biselector CSP.…”
Section: Introductionmentioning
confidence: 97%
“…According to reported literatures, Kromasil‐CHI‐DMB could separate the analytes ketoprofen (TR‐29) 11, binaphthol (TR‐1) 11, 12, mephenytoin (TR‐40) 11, methyl N ‐benzoyl‐phenylalaninate (TR‐27) 17 well and had the tendency to resolve benzoin (TR‐34) 12. In this study, on CSP 2 with similar selector, only ketoprofen (TR‐29) could be separated slightly better than Kromasil‐CHI‐DMB.…”
Section: Resultsmentioning
confidence: 93%
“…Tartaric acid derivatives, such as N , N ′‐diisopropyl‐ L ‐tartardiamide (DIPTA), is a broadly applicable chiral mobile phase additive (CMPA) in silica gel chromatography 8. CSPs of brush type 9, 10 and network copolymer 11–13 based on tartardiamide have been developed successfully to separate a wide variety of racemic solutes under normal‐phase condition. Especially, the chiral columns based on O , O ′‐diaroyl tartardiamide polymer have been commercially available, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In general, bonded‐type CSPs have good solvent resistance but show poor enantioseparation ability compared with coated‐type CSPs. To enhance the chiral resolution ability and broaden the scope of chiral recognition, several biselector bonded‐type CSPs have been developed . Chen et al prapared biselector bonded‐type CSP derived from two D‐tartrates, which showed enhanced enantioseparation ability compared with single selector CSPs .…”
Section: Introductionmentioning
confidence: 99%